ISLAM SEBAGAI AGAMA PEMBEBASAN: KAJIAN FILOSOFIS TERHADAP PEMIKIRAN NURCHOLISH MADJID - Nur Aasaeni, Eli; Ahmad Munirul Hakim (LPPM UIN Sulthan Thaha Saifuddin Jambi, 2025)
This study aims to explore the dimensions of liberation in Islamic teachings through the philosophical perspective of Nurcholish Madjid (Cak Nur). The background to this research is based on the need to understand Islam not only as a ritualistic religion, but also as a liberating force that upholds social justice, equality, and respect for human dignity. The research problem formulation in this study covers three main points: (1) What is the foundation of liberation theology in Islam? (2) What is the concept of liberation in Islam according to Nurcholish Madjid's thinking? (3) What are the philosophical values ​​of liberation in Nurcholish Madjid's thinking? The research method used in this study is a literature study. This research was conducted by collecting, reviewing, and analyzing various literature relevant to the research theme. The data collection technique used is documentation, namely by collecting data from written sources such as Nurcholish Madjid's works, books, journals, and articles relevant to the theme of Islam as a religion of liberation. Meanwhile, the data analysis technique used descriptive-qualitative content analysis, interpreting the text to identify the main themes of Nurcholish Madjid's liberation thought, particularly those related to monotheism, justice, and pluralism. The results of the study indicate that, first, the foundation of liberation theology in Islam rests on the values ​​of monotheism, justice (al-'adl), and social responsibility. This theology directs Muslims to fight against oppression and create a just, equal, and humane society. Second, according to Nurcholish Madjid, liberation is the core teaching of Islam, freeing humanity from all forms of colonialism, both physical and spiritual. Third, the philosophical values ​​of liberation in Cak Nur's thought emphasize that monotheism is a doctrine of liberation from worldly power and oppression. He emphasizes the importance of pluralism, interfaith tolerance, and rejects the exploitation of religion for political gain. Finally, the author recommends that Muslims emphasize monotheism as the basis for social justice and the defense of the oppressed. Islam is understood as a moral force that liberates humanity from oppression, upholds equality, and rejects the politicization of religion.